RESEARCH OF ACHIEVEMENT MOTIVATION’S IMPACT ON THE CAREER ORIENTATIONS OF FUTURE MANAGERS OF ORGANIZATION - Popovych,; Zhigarenko, Igor; Losiyevska, Olga; Dovbenko, Svitlana; Kashyrina, Yevheniia; Shevchenko, Rosina; Piletska, Liybomyra (Revista Inclusiones, 2020)
The purpose of the empirical study is to provide a theoretical justification and empirical study of achievement motivation’s impact on the career orientations of future managers of organizations. It is justified that achievement motivation is one of the types of motivation of the individual, based on the need to succeed. The achievement motive empowers one to realize oneself through career orientation, justifying / disproving his or her social expectations. Research methods: questionnaires, test methods with standardized questionnaires, correlation analysis. It is found that 54.69% (n = 35) of the future managers are career-oriented with “entrepreneurship” and 39.06% (n = 25) of the respondents are career-oriented with “management”. Women’s motivation to avoid failure is higher than men’s at p<.05, which may be due to gender division in society and social expectations. It is established that “motivation to succeed” and “motivation to avoid failure” are two phenomena that can exist simultaneously in the mind of one person. It is expedient to operationalize the received knowledge in the educational process of future managers of organizations.